1990
DOI: 10.2527/1990.68103109x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and tissue distribution from birth to 14 months for three biological types of beef heifers.

Abstract: Thirty-four heifers were sampled randomly from each of the Hereford (He), Charolais (Ch) and Simmental (Si) herds at the U.S. Meat Animal Research Center at 2 d to 14 mo of age to examine body chemical composition and tissue distribution. Six heifers per breed were slaughtered after calorimetry at 2 d, 3 mo, 7 mo, 10 mo and 14 mo of age, and four others at 8 mo, to measure weight of empty body (EBW), water, fat, ash and protein as residual, in four fractions: carcass (CAR), head, hide and shanks (HHS), gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
5
18
0
2
Order By: Relevance
“…Moreover, they displayed lower fractional degradation rates. Comparing the relative body components of empty body weight found in our trial with other breeds, Piemontese cattle showed higher carcass weight, lower weights as regards head plus hide and shank, visceral organs plus blood and gastrointestinal tract than 14 month old Hereford, Charolais and Simmental heifers (Buckley et al, 1990). Furthermore, Piemontese cattle have a prevalence of higher protein tissue content with potential consequences on N efficiency.…”
Section: Biagini and Lazzaronisupporting
confidence: 47%
“…Moreover, they displayed lower fractional degradation rates. Comparing the relative body components of empty body weight found in our trial with other breeds, Piemontese cattle showed higher carcass weight, lower weights as regards head plus hide and shank, visceral organs plus blood and gastrointestinal tract than 14 month old Hereford, Charolais and Simmental heifers (Buckley et al, 1990). Furthermore, Piemontese cattle have a prevalence of higher protein tissue content with potential consequences on N efficiency.…”
Section: Biagini and Lazzaronisupporting
confidence: 47%
“…Nutrition, breed, and physiological status alter weights of the gastrointestinal tract and visceral organs in livestock (Ferrell, 1988). Also, Buckley et al (1990) reported a dramatic increase in internal fat stores in beef heifers between 8 and 14 mo of age, a time that normally corresponds to puberty onset. In the present study, diet and biotype independently altered weights of visceral organs and associated internal fat depots at puberty.…”
Section: Discussionmentioning
confidence: 96%
“…This measurenment will provide valuable information to evaluate FAT at eleven months of age prior to puberty to indicate the need to target puberty earlier. The effects of FAT at specific age can alter the proportion of metabolically active tissues that influences the maintenance requirements (Buckley et al, 1990). Lammoglia et al (2000) observed that feeding 4.4% dietary fat increased the percentage of pubescent heifers by the beginning of the breeding season.…”
Section: Discussionmentioning
confidence: 99%